Factors Associated With Small Bowel Obstruction Following Appendectomy: A Population-Based Study. Issue 18 (May 2016) - Tseng, Chien-Jen; Sun, Ding-Ping; Lee, I-Chen; Weng, Shih-Feng; Chou, Chia-Lin
Abstract : Abstract: Postoperative small bowel obstruction (SBO) is a common complication of appendectomy. This study aimed to assess risk factors for SBO following appendectomy. This retrospective cohort study used the 2006 to 2008 Taiwan National Health Insurance Research Database. We evaluated adult patients with acute appendicitis who underwent open (OA) or laparoscopic appendectomy (LA) between January 1, 2006 and December 31, 2008. Excluded were patients with a history of abdominal surgery and SBO before the index operation, or abdominal surgery between the appendectomy and initial diagnosis of bowel obstruction as an identifiable cause of SBO. Factors thought to influence postoperative SBO were highlighted. The OA and LA cohorts were matched by propensity score, and the hazard ratios (HRs) and 95% confidence interval (CIs) of SBO were calculated. We enrolled 11, 289 patients who underwent OA, and 11, 289 matched controls who underwent LA. OA patients had significant risk of adhesive SBO compared with the LA group (adjusted HR: 1.7, 95% CI: 1.11–2.63). Further analysis revealed that that female sex (adjusted HR: 1.79, 95% CI: 1.17–2.72), CCI score of 1 or ≥2 (adjusted HR: 3.16, 95% CI: 1.76–5.67; adjusted HR: 4.03, 95% CI: 1.57–10.34), complicated appendicitis (adjusted HR: 1.68, 95% CI: 1.05–2.69), treatment in district hospitals increased risk of adhesive SBO. Female sex, complicated appendicitis, more comorbidities, and treatment in district hospitals are factors associated with a risk of SBO after appendectomy. Our findings confirmed that a laparoscopic approach is better than an open approach.